Effect of Magnetic Field and Non-Uniform Surface on Squeeze Film Lubrication - Muthu, P.; Pujitha, V. (Journal of Applied Nonlinear Dynamics, 2026)
In the present paper, the combined effect of magnetic field and nonuniform shape of the surface on squeeze film characteristics is investigated. The non-uniform squeeze film thickness is calculated using Lagrange interpolation technique. Numerical integration procedure is used to obtain the solution for pressure, load carrying capacity. The effects of field parameters on squeeze film characteristics are discussed and are presented graphically. It is observed that externally applied magnetic field and non-uniform shape of the bearing surface enhance the squeeze film lubrication.